Emerging Foodborne Pathogens: Challenges and Strategies for Ensuring Food Safety - Ali Hassan; Muhammad Kashif Iqbal Khan; Summaia Fordos; Ali Hasan; Samran Khalid; Muhammad Zeeshan Naeem; Ali Usman (Biology and Life Sciences Forum, 2023)
This review explores the challenges brought about by emerging foodborne pathogens and the strategies employed to ensure food safety. This study conducted a comprehensive literature review to gather information on the latest trends in foodborne pathogens, their impact on public health, and the measures taken to mitigate their risks. Various scientific databases were utilized to identify relevant articles, research papers, and reports. The research findings highlight the emergence of new and re-emerging foodborne pathogens such as Salmonella, Campylobacter, Escherichia coli, Listeria monocytogenes, and norovirus. These pathogens pose significant health risks and can lead to outbreaks and foodborne illnesses. This study examines the factors contributing to the emergence of these pathogens, including changes in food production, globalization, climate change, and antimicrobial resistance. Furthermore, this study explores the challenges faced in controlling and preventing the spread of these pathogens throughout the food supply chain. It examines issues related to contamination during production, processing, transportation, and consumption. The study also investigates the limitations of current detection methods and the need for improved surveillance systems to identify and respond to emerging pathogens effectively. In terms of strategies for ensuring food safety, this study highlights the importance of implementing preventive measures such as good agricultural practices, proper sanitation, and hygiene protocols. It emphasizes the significance of robust food safety regulations and policies to enforce compliance across the industry. Additionally, this study explores the role of education and awareness campaigns in promoting safe food handling practices among consumers.